Expansão da soja e seu impacto na pecuária de corte no bioma Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Agribusiness is one of the main Brazilian economic activities. Among all Brazilian products, soy stands out, where Brazil is among the largest producers and is the second largest world exporter of grain. Due to the market demand and its high production, soy has been advancing in different regions of the country. This occurs in the Pampa biome, which is characteristic of being the only biome in a single federative unit in the country and that has a close relationship with the economic and cultural formation of Rio Grande do Sul. This study aims to analyze the expansion of soy in the Brazilian Pampa Biome and its impact on livestock systems in the region. Specifically, the aim is to verify the advance of the soy planted area in the Pampa Biome and to analyze the relationship between the increase in soy production and the quantity of the bovine herd in the Pampa. The methodology had a descriptive character with a quantitative approach. Descriptive statistics and linear regression were used as data analysis techniques. The results show an advance of soy over the Pampa, with an average growth of 6.57% per year in the period from 2000 to 2019. It can also be analyzed that for every 100 hectares of soybean, there is an average decrease of 76 head of cattle. Thereat, it is concluded that soy has advanced at an accelerated pace in the biome. Thereby, concerns are raised regarding the degradation of the biome as a result of soy monoculture, and also the cultural and historical aspects that the biome has as a result of cattle-raising activity.
Soy expansion and its impact on beef cattle in the Pampa biome
Keywords: Soja; Bioma Pampa; Sistemas Pecuários; Bovino cultura de corte; Soy; Pampa biome; Livestock systems; Beef culture; CNPQ::CIENCIAS SOCIAIS APLICADAS